Diasporic Pursuits of Justice in Sweden After the Yazidi Genocide - Bostan, Cansu ; 0000-0002-3118-5998 (Opinio Juris, 2025)
As a contribution to the Symposium on Protest and Legal Mobilization, this blog post examines the multifaceted ways in which the Yazidi diaspora in Sweden has pursued justice in the aftermath of the 2014 genocide. It highlights how prosecutions under universal jurisdiction, while symbolically significant, often remain distant from victim-survivors’ lived experiences, and how rituals, commemorations, and demonstrations intertwine with legal claims. In doing so, it frames protest as a transnational “just space” that extends the reach of law while sustaining memory, recognition, and accountability across borders.
Keywords: Yazidi Genocide; diaspora mobilisation; Universal jurisdiction